Perfusion Zones of Extended Transverse Skin Paddles in Muscle-Sparing Latissimus Dorsi Myocutaneous Flaps for Breast Reconstruction. Issue 5 (May 2019) - Koonce, Stephanie L.; Barnavon, Yoav; Newman, Martin I.; Hwee, Yin Kan
Abstract : Background: The authors report their experience using extended transversely oriented skin paddles in muscle-sparing latissimus dorsi pedicled flaps for breast reconstruction as an alternative to thoracodorsal artery perforator flaps. Methods: A retrospective review was conducted of patients who underwent muscle-sparing latissimus dorsi flap pedicled breast reconstruction from January of 2009 to July of 2014 with at least 3-month follow-up. Surgical outcomes and complications were analyzed. Results: Fifty-three patients underwent a total of 81 muscle-sparing latissimus dorsi pedicled flaps for breast reconstruction. Extended transversely oriented skin paddles ranged from 7 to 9 cm vertically by 25 to 35 cm horizontally and were perfused by a strip of latissimus dorsi muscle that was approximately 25 percent of the total muscular volume. Twenty patients had indocyanine green angiography revealing three distinct zones of perfusion in the extended transversely oriented skin paddles. The area of earliest perfusion (designated zone 1) was directly over the muscle containing the perforators. The second best area of perfusion (zone 2) was lateral to the muscle (toward the axilla). The last and relatively least well-perfused area (zone 3) was medial to the muscle (toward the spine). Zone 3 still had adequate viability. There were no flap losses. Minor complications included wound infection [six of 81 (7.4 percent)], fat necrosis [three of 81 (3.7 percent)], and seroma [four of 81 (4.9 percent)]. Conclusions: Muscle-sparing latissimus dorsi pedicled flaps with extended transversely oriented skin paddles are reliable alternatives to thoracodorsal artery perforator flaps for breast reconstruction. Three zones of perfusion were delineated in the extended transversely oriented skin paddles on indocyanine green imaging, and all three zones were viable. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.